The lattice Boltzmann method : principles and practice /: principles and practice. ([2016]) - Krüger, Timm; Kusumaatmaja, Halim; Kuzmin, Alexandr; Shardt, Orest; Silva, Goncalo; Viggen, Erlend Magnus
No abstract available